EVALUASI TIGA MACAM AUKSIN SINTETIK TERHADAP PERTUMBUHAN AKAR LIDAH MERTUA - Tarigan, Puji Lestari (Universitas Nias Raya, 2024)
The propagation of snake plants is efficient when using leaf organs. However, the problem is the growth of roots. Auxin is a plant growth regulator that can stimulate root growth. There are several synthetic auxins and must be applied to obtain the best results in snake plant root growth. The materials used in this experiment were snake plant leaves, synthetic auxin (AUKSIN, Rootone-F, and Atonik), soil, and containers. The tools used included a cutter, ruler, stationery, and camera. Synthetic auxin was applied by smearing it on one part of the leaf base. The experimental design was a Completely Randomized Design, with four treatments: control (without auxin), AUKSIN, Rootone-F, and Atonik. Each treatment had three replications, resulting in twelve experimental units. The data obtained were analyzed using ANOVA and followed by DMRT. The results showed that snake plants treated with Atonik produced the best results and differed from the control significantly.